Artificial intelligence as a tool to enhance social interventions in reducing crime - Tarawneh, Haya H.; Halalsheh, Niveen Z.; Sulaiman, Bahjat Abu; Alhajjaj, Huda A.; Atieh, Nesreen N. (Frontiers in Artificial Intelligence, 2025)
IntroductionThis study explores the significant role of artificial intelligence (AI) in crime reduction, identifies the main challenges hindering its implementation, and examines differences in coping strategies between individuals in Jordan and Saudi Arabia.MethodsThe research surveyed 170 AI professionals, equally divided between the two countries, with an average age of 45.2 years. Data were collected using a specially designed questionnaire assessing perceptions of AI, barriers to adoption, and coping mechanisms.ResultsThe findings indicated that AI plays a significant role in crime reduction. High levels of challenges were reported in implementing AI, and coping strategies related to AI in crime reduction were also assessed at a high level. No statistically significant differences were found in the level of challenges facing AI between Jordanian and Saudi participants.DiscussionThis research contributes to understanding AI’s practical applications in crime prevention and provides valuable insights for policymakers to strengthen AI adoption and overcome existing barriers in the region.